2015
DOI: 10.1371/journal.pntd.0003451
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-Based Detection of Disease Biomarkers in Mouse Models for Chagas Drug Discovery

Abstract: Drug discovery initiatives, aimed at Chagas treatment, have been hampered by the lack of standardized drug screening protocols and the absence of simple pre-clinical assays to evaluate treatment efficacy in animal models. In this study, we used a simple Enzyme Linked Aptamer (ELA) assay to detect T. cruzi biomarker in blood and validate murine drug discovery models of Chagas disease. In two mice models, Apt-29 ELA assay demonstrated that biomarker levels were significantly higher in the infected group compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 34 publications
(59 reference statements)
4
30
0
1
Order By: Relevance
“…However, levels did not return to those seen in non-infected treated mice, suggesting parasitemia was reduced but parasitological cure was not achieved. These results are in agreement with the detection of parasites in the heart and skeletal muscles by PCR and suggest that the assay can be used to assess treatment efficacy in vivo in murine drug discovery models [76]. However, its ability to predict parasitological cure needs to be confirmed.…”
Section: Aptamerssupporting
confidence: 78%
See 1 more Smart Citation
“…However, levels did not return to those seen in non-infected treated mice, suggesting parasitemia was reduced but parasitological cure was not achieved. These results are in agreement with the detection of parasites in the heart and skeletal muscles by PCR and suggest that the assay can be used to assess treatment efficacy in vivo in murine drug discovery models [76]. However, its ability to predict parasitological cure needs to be confirmed.…”
Section: Aptamerssupporting
confidence: 78%
“…Increasing the SELEX rounds and the stringency of the conditions, de Araujo et al found an aptamer (Apt29) with a higher signal for TESA in infected mice and a higher signal-to-noise ratio compared to Apt-L44 [76]. This aptamer was also able to differentiate infected from non-infected mice and predict treatment failure.…”
Section: Aptamersmentioning
confidence: 99%
“…New detection tools continue to be developed. For example, nucleic acid aptamers to identify T. cruzi secreted antigens in serum may surpass the sensitivity of PCR [24], and lineage-specific serology has the potential to define historical exposure to different parasite subtypes [25]. …”
Section: Measuring Parasite Loadsmentioning
confidence: 99%
“…Ongoing investigation of a number of other biomarkers may expand the options available to monitor clinical interventions e.g. [24]. …”
Section: Figurementioning
confidence: 99%
“…Además, se han llevado a cabo ensayos ELA (siglas en inglés, enzyme linked aptamer) para buscar en roedores murinos infestados con T. cruzi posibles biomarcadores que sirvan para la monitorización y evaluación de los futuros fármacos antitripanosomiásicos (41) .…”
Section: Nuevos Avances En El Tratamientounclassified